2015
DOI: 10.1016/j.biortech.2015.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of starch and lipid accumulation in a microalga Chlorella sorokiniana

Abstract: Microalgae have attracted growing attention due to their potential in biofuel feedstock production. However, current understanding of the regulatory mechanisms for lipid biosynthesis and storage in microalgae is still limited. This study revealed that the microalga Chlorella sorokiniana showed sequential accumulation of starch and lipids. When nitrogen was replete and/or depleted over a short period, starch was the predominant carbon storage form with basal levels of lipid accumulation. After prolonged nitroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
33
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(41 citation statements)
references
References 33 publications
8
33
0
Order By: Relevance
“…9c, d, f–i) at day 8. It is indicated that the starch was degraded and lipid content was increased in microalgae which was also proved for C. sorokiniana [27], S. obliquus [28], and C. zofingiensis [29]. The possible mechanism of carbohydrate or starch accumulation is shown in Figs.…”
Section: Resultsmentioning
confidence: 78%
“…9c, d, f–i) at day 8. It is indicated that the starch was degraded and lipid content was increased in microalgae which was also proved for C. sorokiniana [27], S. obliquus [28], and C. zofingiensis [29]. The possible mechanism of carbohydrate or starch accumulation is shown in Figs.…”
Section: Resultsmentioning
confidence: 78%
“…Starch and lipid accumulation are associated in Chlorella (Mizuno et al 2013, Takeshita et al 2014, Li et al 2015. Starch is the primary product of photosynthesis and is metabolized to fatty acids through acetyl-CoA.…”
mentioning
confidence: 99%
“…In addition, the decreased protein degradation and two key enzymes of the glyoxylate cycle, link beta-oxidation, the degradation of fatty acids, with gluconeogenesis and carbon storage. It has been found by Li et al [65] that biosynthesis of starch and lipids benefits in the microalga Chlorella sorokiniana from a more active photosynthesis. Although, the increased expression of enzymes of the glycerophospholipid metabolism indicates a build-up of fatty acids for membrane biosynthesis potentially for growth and cell division, no other pathway indicates growth such as the biosynthesis of amino acids, nucleotides or ribosomes.…”
Section: Discussionmentioning
confidence: 99%